Health Promoting Properties of Behman safed, a root of Centaurea behen Linn.-A Review - Fatima, Gulnar; Siddiqui, Aisha; Jamal, Anwar; Chaudhary, S. (Journal of Drug Delivery and Therapeutics, 2019)
Medicinal plants have been used since prehistoric period for the cure of various diseases. In many developing countries, a large proportion of the population relies on herbal medicine in order to meet health care needs. Although, other health care system exists side by side with modern medicine still, Unani medicine, is  one of the alternate system  maintained its popularity for historical and cultural reasons.1  About 8,000 herbal drugs have been codified in Ayush systems.2 One of them is Centaurea behen Linn., a member of (Asteraceae) family commonly known as safed behmen in Unani medicine.3 It possesses multiple pharmacological actions and medicinal activities such as muqawwi bah (aphrodisiac),kasir riyah (carminative),muhallil auraam (anti-inflammatory), muqawwi qalb (cardio tonic),musakkin (sedative), Mudire-haiz (emmenagogue) etc. It is used preferablly to treat various diseases such as yarqan, (jaundice), hasate kulliya (kidney stone), hasate masana (urinary stone) etc4.  Centaurea species have also shown the presence of flavonoids, sesquiterpene lactones, especially guaianolides, germacranolide type sesquiterpene lactones3 and an alkaloid behamine4 .Hence, this review attempts to compile the information regarding the health promoting properties of centaurea roots in light of recent scientific advancement along with its pharmacological actions, therapeutic uses and pharmacological studies.Keywords: Unani Medicine, Behman safed, Centaurea behen Linn. Pharmacological actions.